Ketamine treatment involves medial prefrontal cortex serotonin to induce a rapid antidepressant-like activity in BALB/cJ mice. (January 2017) - Pham, T.H.; Mendez-David, I.; Defaix, C.; Guiard, B.P.; Tritschler, L.; David, D.J.; Gardier, A.M.
Abstract: Unlike classic serotonergic antidepressant drugs, ketamine, an NMDA receptor antagonist, exhibits a rapid and persistent antidepressant (AD) activity, at sub-anaesthetic doses in treatment-resistant depressed patients and in preclinical studies in rodents. The mechanisms mediating this activity are unclear. Here, we assessed the role of the brain serotonergic system in the AD-like activity of an acute sub-anaesthetic ketamine dose. We compared ketamine and fluoxetine responses in several behavioral tests currently used to predict anxiolytic/antidepressant-like potential in rodents. We also measured their effects on extracellular serotonin levels [5-HT]ext in the medial prefrontal cortex (mPFCx) and brainstem dorsal raphe nucleus (DRN), a serotonergic nucleus involved in emotional behavior, and on 5-HT cell firing in the DRN in highly anxious BALB/cJ mice. Ketamine (10 mg/kg i.p.) had no anxiolytic-like effect, but displayed a long lasting AD-like activity, i.e., 24 h post-administration, compared to fluoxetine (18 mg/kg i.p.). Ketamine (144%) and fluoxetine (171%) increased mPFCx [5-HT]ext compared to vehicle. Ketamine-induced AD-like effect was abolished by a tryptophan hydroxylase inhibitor, para -chlorophenylalanine (PCPA) pointing out the role of the 5-HT system in its behavioral activity. Interestingly, increase in cortical [5-HT]ext following intra-mPFCx ketamine bilateral injection (0.25 μg/side) was correlated with its AD-like activity as measured on swimming duration in the FST in the same mice. Furthermore, pre-treatment with a selective AMPA receptor antagonist (intra-DRN NBQX) blunted the effects of intra-mPFCx ketamine on both the swimming duration in the FST and mPFCx [5-HT]ext suggesting that the AD-like activity of ketamine required activation of DRN AMPA receptors and recruited the prefrontal cortex/brainstem DRN neural circuit in BALB/c mice. These results confirm a key role of cortical 5-HT release in ketamine's AD-like activity following the blockade of glutamatergic NMDA receptors. Tight interactions between mPFCx glutamatergic and serotonergic systems may explain the differences in this activity between ketamine and fluoxetine in vivo . This article is part of the Special Issue entitled 'Ionotropic glutamate receptors'. Highlights: Unlike fluoxetine, ketamine induced persistent antidepressant-like effect in mice. Ketamine increase cortical, but not [5-HT]ext in the dorsal raphe nucleus. Increases in cortical 5-HT is required for ketamine's antidepressant-like activity. Activation of DRN AMPA receptors and of the prefrontal cortex/brainstem DRN neural circuit are required for ketamine's antidepressant-like activity in BALB/c mice.